2016
DOI: 10.3390/horticulturae2040017
|View full text |Cite
|
Sign up to set email alerts
|

Organic Horticulture in India

Abstract: During the previous three decades, organic produce has attracted the attention of a growing health-conscious population across the globe. Both international and domestic communities are becoming aware of issues like agrochemical residues, produce quality, and food safety. Worldwide, over 37.5 million ha of land (0.87% of total agricultural land) is being managed organically by 1.9 million producers in 164 countries. In addition, there is another 31 million ha certified for wild harvest collection. Global sales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…There is immense scope for organic production of vegetable crops in India since the agricultural sector has enormous organic resources like crop residues, livestock and other bio-products from agro industries. Organic farming is growing at a rapid pace among Indian farmers and entrepreneurs, particularly in rainfed and hilly areas where fertilizer consumption is less than 25 kg/ha/year [13].…”
Section: Prospects and Constraints Of Organic Vegetable Productionmentioning
confidence: 99%
“…There is immense scope for organic production of vegetable crops in India since the agricultural sector has enormous organic resources like crop residues, livestock and other bio-products from agro industries. Organic farming is growing at a rapid pace among Indian farmers and entrepreneurs, particularly in rainfed and hilly areas where fertilizer consumption is less than 25 kg/ha/year [13].…”
Section: Prospects and Constraints Of Organic Vegetable Productionmentioning
confidence: 99%
“…India is exporting organic products to all the continents of the world of which the largest share goes to EU (44.12%) followed by USA (19.2%). Mitra and Devi (2015) reported that worldwide, over 37.5 million ha of land (0.87% of total agricultural land) is being managed organically by 1.9 million producers in 164 countries. In addition, there is another 31 million ha certified for wild harvest collection.…”
Section: Organic Scenario World and Indian Scenariomentioning
confidence: 99%
“…Most of the farms in remote and marginal areas are subsistence type. Organic farming is growing rapidly among Indian farmers and entrepreneurs, especially in low productivity areas, rain-fed zones, hilly areas and the northeastern states where fertilizer consumption is less than 25 kg/ha/year (Mitra and Devi, 2016). In fact, North Eastern Region (NER) is considered as home to some niche crops like Assam lemon, Joha rice, medicinal rice and passion fruits which has high market demands and accounts for 45 per cent of total pineapple production in India (Munda et al, 2007).…”
Section: Scope and Prospects Of Organic Farmingmentioning
confidence: 99%
“…In fact, North Eastern Region (NER) is considered as home to some niche crops like Assam lemon, Joha rice, medicinal rice and passion fruits which has high market demands and accounts for 45 per cent of total pineapple production in India (Munda et al, 2007). Uttaranchal and Northeast states have declared themselves "organic-farming states" where as Mizoram and Sikkim declared their intentions to move to total organic farming (Mitra and Devi, 2016). Sikkim has become India's first fully organic state by implementing organic practices on approximately 75,000 ha of agricultural land (Sikkim, 2016).…”
Section: Scope and Prospects Of Organic Farmingmentioning
confidence: 99%